2000
DOI: 10.1101/gr.150300
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Genetic Maps in Wild Emmer Wheat, Triticum dicoccoides: Genome-Wide Coverage, Massive Negative Interference, and Putative Quasi-Linkage

Abstract: The main objectives of the study reported here were to construct a molecular map of wild emmer wheat, Triticum dicoccoides, to characterize the marker-related anatomy of the genome, and to evaluate segregation and recombination patterns upon crossing T. dicoccoides with its domesticated descendant Triticum durum(cultivar Langdon). The total map length exceeded 3000 cM and possibly covered the entire tetraploid genome (AABB). Clusters of molecular markers were observed on most of the 14 chromosomes. AFLP (ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
103
1
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(115 citation statements)
references
References 69 publications
(101 reference statements)
9
103
1
2
Order By: Relevance
“…We confirmed this interference in a different cross where the screening of .1400 F 2 CsRe using two markers separated by 12 cM and localized in the distal part of the short arm showed an absence of double COs (P-value ¼ 0.015, data not shown). In wheat and barley, Peng et al (2000) and Esch and Weber (2002) reported negative interference within short distances. However, in contrast to our study that is based on doubled-haploid populations, Peng et al (2000) used F 2 plants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We confirmed this interference in a different cross where the screening of .1400 F 2 CsRe using two markers separated by 12 cM and localized in the distal part of the short arm showed an absence of double COs (P-value ¼ 0.015, data not shown). In wheat and barley, Peng et al (2000) and Esch and Weber (2002) reported negative interference within short distances. However, in contrast to our study that is based on doubled-haploid populations, Peng et al (2000) used F 2 plants.…”
Section: Discussionmentioning
confidence: 99%
“…In wheat and barley, Peng et al (2000) and Esch and Weber (2002) reported negative interference within short distances. However, in contrast to our study that is based on doubled-haploid populations, Peng et al (2000) used F 2 plants. Estimation of the coefficient of coincidence with this type of population is biased because two independent gametes are considered as one.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To minimize the effect of negatively interacting loci causing mortality on the linkage map reconstruction due to a phenomenon commonly referred to as quasi-or pseudolinkage (Korol et al 1989;Lorieux et al 1995a,b;Liu 1998;Weston et al 1999;Peng et al 2000), we considered only F 2 hybrid embryos for linkage analysis. We first evaluated the mapping population (N ¼ 225) by analyzing markers for missing information and MTRD.…”
Section: Stocksmentioning
confidence: 99%
“…The last assumption is especially supported by allele distribution at GWM537 (Figure 1). (1998), the distance of GWM 218 also referred to the map of Peng et al (2000). c m, n, and k symbolize repeat number.…”
Section: Ssr Allele Distribution With Size Clusters and Constraintsmentioning
confidence: 99%